2016
DOI: 10.1103/physrevd.93.035007
|View full text |Cite
|
Sign up to set email alerts
|

Search for mirror quarks at the LHC

Abstract: Observation of non-zero neutrino masses at a scale ∼ 10 −1 − 10 −2 eV is a major problem in the otherwise highly successful Standard Model. The most elegant mechanism to explain such tiny neutrino masses is the seesaw mechanism with right handed neutrinos. However, the required seesaw scale is so high, ∼ 10 14 GeV, it will not have any collider implications. Recently, an explicit model has been constructed to realize the seesaw mechanism with the right handed neutrinos at the electroweak scale. The model has a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…The phenomenology of mirror quarks and leptons was briefly discussed in [9] and a detailed analysis of mirror quarks was presented in [13]. It suffices to mention here that mirror fermions decay into SM fermions through the process q M → qφ S , l M → lφ S with φ S "appearing" as missing energy in the detector.…”
Section: Review Of the Scalar Sector Of The Ew ν R Model Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenology of mirror quarks and leptons was briefly discussed in [9] and a detailed analysis of mirror quarks was presented in [13]. It suffices to mention here that mirror fermions decay into SM fermions through the process q M → qφ S , l M → lφ S with φ S "appearing" as missing energy in the detector.…”
Section: Review Of the Scalar Sector Of The Ew ν R Model Inmentioning
confidence: 99%
“…In a previous work [13], we discussed the signals of the electroweak ν R model at the LHC arising from the pair productions of the mirror quarks as developed in [9] and the subsequent extensions of the model satisfying all the constraints. We found that for the prompt decays of the mirror quarks plus almost massless neutral scalar (present in the model), the mass of the lightest mirror quark as low as 600 GeV is allowed from the 8 TeV data assuming this branching ratio to be 100%.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenology of mirror quarks and leptons was briefly discussed in [11][12][13][14][15] and a detailed analysis of mirror quarks will be presented in [24]. It suffices to mention here that mirror fermions decay into SM fermions through the process q M → qφ S , l M → lφ S with φ S "appearing" as missing energy in the detector.…”
Section: Jhep09(2015)001mentioning
confidence: 99%
“…Tiny Dirac masses can also be given via small VEVs of Higgs singlets with Y = 0. This is the electroweak scale see-saw mechanism in mirror fermion model which is testable at the LHC [74,119].…”
Section: Motivationmentioning
confidence: 99%
“…The phenomenology of mirror quarks and leptons was briefly discussed in [70] and a detailed analysis of mirror quarks was presented in [74]. It suffices to mention here that mirror fermions decay into SM fermions through the process q M → qφ S , l M → lφ S with φ S "appearing" as missing energy in the detector.…”
Section: Electroweak Precision Constraints On the Ew ν R Model [71]mentioning
confidence: 99%